Settlement and Release in European Legislation - V. V. Rasskazova (Bulletin of Kharkiv National University of Internal Affairs)
Since the current contractual practice demonstrates the active use of settlement and release construction by the parties of civil legal relations as one of the most flexible instruments of termination of an obligation, the issue of ensuring unity in the interpretation and practice of this legal institution remains relevant. The subject matter of this study is the norms of civil law of different Member States of the European Union, and the purpose is the study of the conceptual approaches of other states to the legislative consolidation of settlement and release structure, its recognition as one of the ways to terminate the obligation and specific features of the interpretation and application of this institution that will make it possible to enlarge the view on the essence and role of settlement and release within the system of grounds for the termination of civil obligation and national contractual practice.